The effect of temporary uterine artery ligation on laparoscopic myomectomy to reduce intraoperative blood loss: A retrospective case–control study. (August 2022) - Hiratsuka, Daiki; Isono, Wataru; Tsuchiya, Akira; Okamura, Asuka; Fujimoto, Akihisa; Nishii, Osamu
Abstract: Objective: To reduce intraoperative blood loss in laparoscopic myomectomy, uterine artery occlusion or temporary uterine artery clipping have been employed. Recently, in addition to these techniques, temporary uterine artery ligation has been reported as a new method that has less invasive effects on fertility and needs no special devices to be used. This study aimed to evaluate the effect of temporary uterine artery ligation to minimize intraoperative blood loss during laparoscopic myomectomy. Study Design: This was a retrospective case-control study at the department of Obstetrics and Gynaecology, University Hospital Mizonokuchi, Teikyo University School of Medicine. A total of 264 patients with uterine leiomyoma who underwent laparoscopic myomectomy were enrolled in this study. We divided the patients into two groups, those who underwent temporary uterine artery ligation (52 patients) and those who did not (212 patients) and compared the operation time, blood loss volume, and other indexes. Second, to identify influential factors, we assessed the effects of 11 representative factors on massive blood loss or a prolonged operation time using multivariate analysis. Results: The intraoperative blood loss volume was decreased by approximately half with the addition of temporary uterine artery ligation (75.1 ± 73.6 ml vs. 158.5 ± 233.2 ml, p = 0.011), but the operation time was longer (200.5 ± 46.9 min vs. 160.1 ± 51.3 min, p < 0.001). Among the 264 patients, 25 patients (9/52 in the case group and 16/212 in the control group) had a prolonged operation time (≥ 240 min), and 24 patients (1/52 in the case group and 23/212 in the control group) experienced massive blood loss (≥ 400 ml). In the multivariate analysis, high body mass index, concomitant surgery and temporary uterine artery ligation showed a positive association with a prolonged operative time, and the presence of single leiomyoma showed a negative association. Concomitant surgery and the presence of large leiomyoma showed a positive association with massive blood loss, and temporary uterine artery ligation showed a negative association. Conclusions: By performing temporary uterine artery ligation during laparoscopic myomectomy, the volume of intraoperative blood loss could be decreased, especially in patients with large leiomyomas. However, because this procedure prolongs the operation time, there is still room for improvement. Highlights: The surgical technique for laparoscopic myomectomy is introduced. Temporary uterine artery ligation decreases the volume of intraoperative blood loss. Temporary uterine artery ligation is less invasive than permanent occlusion. Temporary uterine artery ligation does not require the use of any special devices, such as clips.